Randomized clinical trial of selective versus routine preoperative duplex ultrasound imaging before arteriovenous fistula surgery. (20th February 2014) - Smith, G E; Barnes, R; Chetter, I C
Abstract: Background: Anatomical suitability for arteriovenous fistula (AVF) formation was formerly determined by clinical examination alone. There are potential benefits from imaging to assess anatomical suitability. Existing studies examined the role of routine preoperative ultrasonography versus clinical examination alone. The role of a selective duplex ultrasound imaging policy is unknown. This study aimed to compare a policy of selective versus routine ultrasound assessment before AVF formation. Methods: All patients referred for fistula formation were assessed for inclusion. Suitable patients were randomized to either routine or selective preoperative ultrasound imaging; selective imaging was performed only when clinical criteria were not met. The primary outcome measures were site of AVF formation and 30-day primary failure rate, and secondary outcome measures included the rate of complications. Results: A total of 106 patients were assessed, and 94 were randomized: 47 to selective and 47 to routine duplex ultrasonography. The groups were well matched for age, co-morbidities and medications. The primary failure rate (29 per cent overall) was not significantly different between the selective and routine imaging groups: 36 per cent (14 of 39) and 21 per cent (8 of 38) respectively ( P = 0·144). There were no significant differences in the sites of AVF formation or complication rates. Conclusion: Routine preoperative ultrasound vessel imaging did not significantly reduce early failure rates, influence the site of AVF formation or reduce complications. If clinical evaluation detects anatomy suitable for AVF formation, duplex imaging may not be needed. Registration number: NCT01004627 (http://www.clinicaltrials.gov ). Abstract : No difference